Surface Emissions Modulate Indoor SVOC Concentrations through Volatility-Dependent Partitioning - Lunderberg, David M; Kristensen, Kasper; Tian, Yilin; Arata, Caleb; Misztal, Pawel K.; Liu, YingJun; Kreisberg, Nathan; Katz, Erin F; DeCarlo, Peter F; Patel, Sameer; Vance, Marina E; Nazaroff, William W.; et al. (Environmental Science & Technology, 2020)
Measurements by semivolatile thermal desorption aerosol gas chromatography (SV-TAG) were used to investigate how semivolatile organic compounds (SVOCs) partition among indoor reservoirs in (1) a manufactured test house under controlled conditions (HOMEChem campaign) and (2) a single-family residence when vacant (H2 campaign). Data for phthalate diesters and siloxanes suggest that volatility-dependent partitioning processes modulate airborne SVOC concentrations through interactions with surface-laden condensed-phase reservoirs. Airborne concentrations of SVOCs with vapor pressures in the range of C13 to C23 alkanes were observed to be correlated with indoor air temperature. Observed temperature dependencies were quantitatively similar to theoretical predictions that assumed a surface-air boundary layer with equilibrium partitioning maintained at the air-surface interface. Airborne concentrations of SVOCs with vapor pressures corresponding to C25 to C31 alkanes correlated with airborne particle mass concentration. For SVOCs with higher vapor pressures, which are expected to be predominantly gaseous, correlations with particle mass concentration were weak or nonexistent. During primary particle emission events, enhanced gas-phase emissions from condensed-phase reservoirs partitioned to airborne particles, contributing substantially to organic particulate matter. An emission event related to oven-usage was inferred to deposit siloxanes in condensed-phase reservoirs throughout the house, leading to the possibility of reemission during subsequent periods with high particle loading.